A Case of Oral Rehabilitation Using a Bone Graft and Implant Overdenture for a Severe Ridge Defect - OHKUBO, Chikahiro; KURIHARA, Daisuke; SUZUKI, Yasunori; KOKUBO, Yuji; NAKAOKA, Kazutoshi (Journal of Japanese Society of Oral Implantology, 2024)
When implant placement in the existing bone is not possible, bone regeneration is an essential procedure for long-term functional and esthetic stability of the implant. This clinical report describes implant treatment using a bone graft and implant overdenture (IOD) for a severe bone defect.The patient was a 25-year-old man with the chief complaint of swelling of the left buccal region. CT images showed a unilocular radiolucent lesion extending from the maxillary anterior region to the maxillary sinus. The lesion included an impacted tooth and root resorption of 21 to 24 was observed. A biopsy suggested that it was a glandular odontogenic cyst (GOC). Cystectomy was performed with root canal filling and apicoectomy of 21 to 24. Nine months later, tooth extraction of 21 to 24 was performed because of increased mobility, and an immediate denture was inserted. Reconstruction of the alveolar ridge using particulate cancellous bone and marrow (PCBM) was carried out with a titanium mesh tray. Nine months after the PCBM graft, 3 dental implants were placed into the reconstructed bone. After confirming the osseointegration, an implant-supported prosthesis was fabricated. A telescopic system was selected as the retainer for cleanability. The patientʼs satisfaction was improved by the IOD. As of 6 years after IOD placement, implant loss, bone resorption, decrease of retention force, and denture breakage have not been observed.